Kebijakan Kriminal Di Bidang Konservasi Keanekaragaman Hayati - Saifullah Saifullah (ULUL ALBAB Jurnal Studi Islam, 2018)
The study is aimed at analyzing the implementation and the perspectives of criminal policies in the field of biodiversity conservation. Reevaluation on penal policies is focused on five concepts. Therefore, it is necesarry to recheck the terminology of flora and fauna using a method of categorizing for all flora and fauna becoming the results of the real development in the field in relation to the category standard of IUCN using the final version of 1994 or CITES Appendix,. Non penal policies which have been applied by the program organizers are adapted to the data field through PRA (Participatory Rural Appraisal) studies. Reevaluation on non penal policies have been elaborated in details in both two programs Reevaluation mentioned above is useful for constructing perspective by considering the recommendation on criminal policies in the United Nations Congress: CITES, KTT Land Document in Rio de Janeiro 1992, and Global Biodiversity Strategies of 1992, national conferences for experts of criminal laws of natural environment and comparative study in criminal policies on natural environment in other countries. The theoretical and practical contributions of criminal policies in biodiversity conservation are valued as a paradigm in the contexts of: (1) the effects of internal and external affairs based on democracy principles on the existence of criminal policy, (2) the position of criminal policy in the paradigm of law reformation in Indonesia.